The effect of alkaline treatment on the mechanical properties of treated sugar palm yarn fibre reinforced unsaturated polyester composites reinforced with different fibre loadings of sugar palm fibre - Norizan, Mohd Nurazzi; Abdan, Khalina; Salit, Mohd Sapuan; Mohamed, Rahmah (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this paper was to describe the effects of treated sugar palm yarn fibre loading on the mechanical properties of reinforced unsaturated polyester composites. Composites with varying fibre loads (10, 20, 30, 40 and 50 wt. %) were prepared using a hand-layup process. The composites were tested for tensile, flexural and impact strength according to ASTM D3930, ASTM D790 and ASTM D256 standards, respectively. The results showed that an increase in fibre loading of up to 30 wt. % increased tensile strength (31.27 MPa), tensile modulus (4.83 GPa), flexural strength (58.14 MPa) and modulus (4.48 GPa). Maximum loading can be attained at 40 wt. % of fibre loading for impact strength (38 kJ/ m2). The effectiveness of stress transfer mechanism through the fibre-matrix interaction, coupled with the optimization of fibre loading in resisting fracture and failure, boosts the overall mechanical performance of sugar palm composite.